2015
DOI: 10.2485/jhtb.24.401
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Sandwich Enzyme-Linked ImmunoSorbent Assay (ELISA) System for Quantitation of CD81

Abstract: CD81 belongs to a family of cell-surface proteins (tetraspanins) that have four transmembrane domains and two outer-membrane loops. CD81 has been shown to be up-regulated in rheumatoid arthritis (RA) synoviocytes and is involved in the progression of RA through the promotion of synoviolin expression. Recently, we showed that small interfering RNA targeting CD81 (CD81 siRNA) ameliorates paw swelling in collageninduced arthritic (CIA) rats. CD81 siRNA also decreases the expression of TNF-in SW982 cells. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…It was reported that TNF- and IL-1 induce synoviolin expression through activation of Erk1/2-ETS1 signalregulated kinase in synovial fibroblasts 18) . We have previously shown that CD81 mediates TNF-á-induced synoviolin expression in SW982 cells 12) . Thus, a similar mechanism acting through activation of the Erk1/2-ETS1 signal-regulated kinase may act in the CD81-synoviolin pathway and lead to CD81-dependent proliferation of synoviocytes in RA.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It was reported that TNF- and IL-1 induce synoviolin expression through activation of Erk1/2-ETS1 signalregulated kinase in synovial fibroblasts 18) . We have previously shown that CD81 mediates TNF-á-induced synoviolin expression in SW982 cells 12) . Thus, a similar mechanism acting through activation of the Erk1/2-ETS1 signal-regulated kinase may act in the CD81-synoviolin pathway and lead to CD81-dependent proliferation of synoviocytes in RA.…”
Section: Discussionmentioning
confidence: 95%
“…This eluted fraction was concentrated and the titer of IgG1 MAb was analyzed by ELISA. These IgG1 MAbs showed a higher titer to the antigen compared with the titer of antiserum 11,12) .…”
Section: Production Of Igg Monoclonal Antibodiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Given this, diagnosis using CD81 or its derivatives might open new avenues for RA treatment. We have already established a highly sensitive sandwich enzyme-linked immunosorbent assay (ELISA) system for quantitating CD81 by using two MAbs against CD81 that recognize different epitopes 13) . Further improvement of this system and the identifi cation of possible molecules for RA diagnosis are in progress.…”
Section: Discussionmentioning
confidence: 99%